Value of corneal epithelial and Bowman’s layer vertical thickness profiles generated by UHR-OCT for sub-clinical keratoconus diagnosis - Xu, Zhe (Sci Rep, 2016)
Ultra-high resolution optical coherence tomography (UHR-OCT) can image the corneal epithelium and Bowman’s layer and measurement the thicknesses. The purpose of this study was to validate the diagnostic power of vertical thickness profiles of the corneal epithelium and Bowman’s layer imaged by UHR-OCT in the diagnosis of sub-clinical keratoconus (KC). Each eye of 37 KC patients, asymptomatic fellow eyes of 32 KC patients, and each eye of 81 normal subjects were enrolled. Vertical thickness profiles of the corneal epithelium and Bowman’s layer were measured by UHR-OCT. Diagnostic indices were calculated from vertical thickness profiles of each layer and output values of discriminant functions based on individual indices. Receiver operating characteristic curves were determined, and the accuracy of the diagnostic indices were assessed as the area under the curves (AUC). Among all of the individual indices, the maximum ectasia index for epithelium had the highest ability to discriminate sub-clinical KC from normal corneas (AUC = 0.939). The discriminant function containing maximum ectasia indices of epithelium and Bowman’s layer further increased the AUC value (AUC = 0.970) for sub-clinical KC diagnosis. UHR-OCT-derived thickness indices from the entire vertical thickness profiles of the corneal epithelium and Bowman’s layer can provide valuable diagnostic references to detect sub-clinical KC.